1978
DOI: 10.1073/pnas.75.3.1265
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypically cryptic EcoRI endonuclease activity specified by the ColE1 plasmid.

Abstract: (1), is encoded by genes located on a bacterial plasmid that has been designated pMB1 (2); a second site-specific enzyme, which methylates the adenosine at the center of the nucleotide sequence comprising the EcoRI endonuclease cleavage site (3) thereby rendering the site insusceptible to cleavage, is also specified by the pMB1 plasmid. It has been reported that a large segment of the pMB1 plasmid is homologous with another widely studied bacterial plasmid, ColEl (2). Since ColEl DNA is cleaved in vitro by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Shibata et al (33) showed the presence ofa site-specific endonuclease in B. subtilis Marburg (strain 168) that can cleave in vitro the DNA of bacteriophages grown on the same strain. This observation suggests lack of significant modification and restriction in vivo similar to that of the EcoRI enzyme system recently reported (24). In general, only a weak restriction type of nuclease activity has been demonstrated in B. subtilis (38).…”
Section: Discussionsupporting
confidence: 72%
“…Shibata et al (33) showed the presence ofa site-specific endonuclease in B. subtilis Marburg (strain 168) that can cleave in vitro the DNA of bacteriophages grown on the same strain. This observation suggests lack of significant modification and restriction in vivo similar to that of the EcoRI enzyme system recently reported (24). In general, only a weak restriction type of nuclease activity has been demonstrated in B. subtilis (38).…”
Section: Discussionsupporting
confidence: 72%
“…Less epidemiological attention is normally paid to small mobilizable plasmids. However, they are also carriers of antibiotic resistance genes (110)(111)(112)(113), as well as competition weapons, such as bacteriocins (113)(114)(115)(116) and restriction-modification enzymes (117)(118)(119)(120). They rely on conjugative plasmids as helpers for their conjugative transmission.…”
Section: Most Prevalent Plasmid Groups In E Colimentioning
confidence: 99%